Perspektif Hukum Islam Tentang Seni - Suhendra, Darmiko (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2017)
Art is defined as the expertise to disclose or express ideas and thoughts a esthetics, including the ability and imagination to realize the creation of objects or the work atmosphere capable of inflicting a sense beautiful. Art is diverse and most of it always questionable in terms of Islamic law. In general, the art divided into two: first, sculpture, painting and drawing. And second, sound art. The main problem in sculpture, painting and drawing is if the object of animate beings, because on the one hand there are numbers of hadith that prohibit making images that are either raised or incurred and three dimensions. While on the other hand it has been commonly done in the community, especially in the natural environment that is fertile and rich with a variety of animals created by God as our State that inspired the artists. In addition, the sculpture on the side can be an expression of sheer beauty, it also has benefits for lessons and so on. Furthermore, sound art is a universal cultural phenomenon, practiced by many nations. In the time of the Prophet himself has been known to sing and play music. In terms of general principles of religious teachings that sound art including mu'amalat dunyawiyyah category. Restrictions on the arts (sculpture, painting, drawing, and sound) for their prudence of Muslims. Prudence was intended that they do not fall to the things that are contrary to the values of Islam which is the focal point at that time. Art as an aesthetic manifestation of the spirit of monotheism and not a waste of money but the art necessary for the improvement of human life, promotion of the dignity and the dignity and refining the soul and the mind. If so the purpose of art, then it is possible that the skill and sunnah favor, not against it.